HCl and ClO in activated Arctic air; first retrieved vertical profiles from TELIS submillimetre limb spectra - de Lange, A.; Birk, Manfred; de Lange, G.; Friedl-Vallon, F.; Kiselev, O.; Koshelets, V.; Maucher, G.; Oelhaf, H.; Selig, A.; Vogt, Peter; Wagner, Georg; Landgraf, J. (Atmospheric Measurement Techniques, 2012)
The first profile retrieval results of the Terahertz and submillimeter Limb Sounder (TELIS) balloon instrument are presented. The spectra are recorded during a 13-h balloon flight on 24 January 2010 from Kiruna, Sweden. The TELIS instrument was mounted on the MIPAS-B2 gondola and shared this platform with the Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) and the mini- Differential Optical Absorption Spectroscopy (mini-DOAS) instruments. The flight took place within the Arctic vortex at an altitude of 34 km in chlorine activated air, and both active (ClO) and inactive chlorine (HCl) were measured over an altitude range of respectively 16Ã¢ÂÂ32 km and 10Ã¢ÂÂ 32 km. In this altitude range, the increase of ClO concentration levels during sunrise has been recorded with a temporal resolution of one minute. During the daytime equilibrium, a maximum ClO level of 2.1ÃÂ±0.3 ppbv has been observed at an altitude of 23.5 km. This equilibrium profile is validated against the ClO profile by the satellite instrument Microwave Limb Sounder (MLS) aboard EOS Aura. HCl profiles have been determined from two different isotopes Ã¢ÂÂ H35Cl and H37Cl Ã¢ÂÂ and are also validated against MLS. The precision of all profiles is well below 0.01 ppbv and the overall accuracy is therefore governed by systematic effects. The total uncertainty of these effects is estimated to be maximal 0.3 ppbv for ClO around its peak value at 23.5 km during the daytime equilibrium, and for HCl it ranges from 0.05 to 0.4 ppbv, depending on altitude. In both cases the main uncertainty stems from a largely unknown non-linear response in the detector.